A Forensic Analysis of Video Streaming Activities on Android Applications - Ahmad, Adil; Hussain, Mehdi (Universitas Ahmad Dahlan, 2022)
Mobile applications of video streaming platforms store a lot of information on mobile devices which can have both positive and negative impacts. Positive, in the sense that it could assist law enforcement agencies in solving crime, and the negative impact is that it could be accessed by malicious actors. In this study, we forensically investigate the Netflix, Amazon Prime Video, and iFlix android applications. The major focus is on identifying stored artifacts on the mobile devices left behind by the android video streaming applications. It will give law enforcement agencies and forensic investigators a clear direction when it comes to extracting evidence to solve a crime. On the other hand, it will notify the mobile application developers on how to further improve the security of their mobile applications.